KUNYIT (CURCUMA DOMESTICA VAL) TERNYATA DAPAT MENAWARKAN RACUN PADA HATI YANG DIBERI CCl4 - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1994)
It has been known that turmeric (Curcuma domesitica) is a useful drugs as analgetics (killing pain), antiseptic and preventing from intoxicated. Yet, the scientific proof to that fact it still needs to described. This experiment aimed to see the effectiveness of turmeric in preventing from tetrachlor carbon hepatotoxicity (CCI4) as the destroyer agent of liver cell. To reach this aim, 20 white rats had been used as the media of the trial. These 20 white rats were divided into 4 groups. Each group consists of 5 white rats. The first group was the control, the second group was the comparison. The rat in the second . group were given 40% turmeric infusion. The third group was the rat which were given CCI4, 1.25 ml/kg/weight. The fourth group is the rat which were given CCI4, 1.25 mi/kg/weight. After 24 hours, all rat were sacrificed and the livers were examined. The experiment showed that CCI4 could cause fat degeneration in the liver and rats were given 40% turmeric infusion could prevent damage the livers.